The effect of coaching frequency and tenure on engagement and turnover in the New Zealand Police Service : a conditional process analysis : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies at Massey University, Albany, New Zealand - Mowat, Jesse William (Massey University, 2022)
To realise the vision of making New Zealand the safest country in the world, in 2017 the New Zealand Police Service (NZ Police) introduced the Police High Performance Framework (PHPF) to equip and enable the organisation’s 14,500 strong workforce to perform to its best. As a part of the framework, the organisation encouraged its supervisors to deliver monthly one-on-one job-related coaching to each of their direct reports. Notwithstanding the allure of the ‘supervisor-as-coach’ model, there is debate about how and when it delivers the favourable outcomes that organisations anticipate. Via the post-positivist research tradition and through the lens of leader-member exchange theory, this study helps fill this research-gap by exploring the direct and mediated effect of coaching frequency on employee engagement, and coaching frequency on intention to turnover, and exploring whether employee tenure (length-of-service) has a moderating influence. Using conditional process analysis, three linear regression models were fitted to survey-data collected from 150 NZ Police employees. It was found that coaching frequency has a tiny but statistically significant effect on employee engagement and intention to turnover both directly, and when mediated by the perceived quality of the employee coaching relationship (PQECR). Additionally, the study found that the PQECR has a small, positive, direct effect on employee engagement, and a moderate, negative, direct effect intention to turnover. Surprisingly, it was found that tenure has no moderating effect whatsoever. Therefore, to fully benefit from the supervisor-as-coach model, NZ Police should focus on two main things. The first is to equip the organisation’s supervisors by providing them with ongoing training on how to strengthen their direct reports’ PQECR. The second is to make structural changes that enable the organisation’s supervisors to coach each of their direct reports (regardless of tenure) on at least a monthly basis as prescribed.
Keywords: 350503 Human resources management